Analisis Kualitas Layanan Petugas Pendaftaran Poliklinik Pasien Rawat Jalan di RS X Jakarta Selatan 2023 - Erik Aria Winata; Mohamad Yaser; Novrida Tambunan (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
One of the important indicators in hospital quality standards is the level of patient satisfaction with the services provided. Therefore, improving the quality of health services is very crucial, not only in the medical aspect, but also in terms of communication and empathy of health workers to patients. This study aims to determine the description of the quality of service of registration staff at the outpatient polyclinic of General Hospital X, South Jakarta, in 2023, based on patient perceptions. This study is a quantitative study with a descriptive approach, conducted on 50 respondents. Data were collected using a questionnaire covering five dimensions of SERVQUAL: Tangibles, Reliability, Responsiveness, Assurance, and Empathy. Data analysis was carried out by presenting the frequency distribution and percentage of each service dimension. The results showed that: in the Tangibles dimension, 66% of respondents rated it good and 34% less good; Reliability, 70% good and 30% not good; Responsiveness, 52% good and 48% not good; Assurance, 72% good and 28% not good; and Empathy, 66% good and 34% less good. In conclusion, although most respondents rated the service of the registration staff as good, there are still aspects that need to be improved. Improving the overall quality of service, especially in the dimensions of Responsiveness and Empathy, is needed as a strategic step in an effort to increase patient satisfaction and loyalty.